(3cJGH aj GdWHs - (3CHh LYaQ CMeO Hf YjSi GdgGTej GdYdhjs
(3ChdgG (B:s
(3GdMeO ddg, GYde CQTOfG Gddg hEjGce Cf UfGYI GdWH GdJi cGfJ CSfi GdUfGFY aj LejY GdCeUGQ hGdeOf s
(3BNQgG (B:s
(3eSCdI(B: (3eGHGd TYQ GdMGLHjf hTYQ GdCTaGQ hdG jTjH hZjQg ef TYQ GddMjI jTjH? GdLhGH hGLJeGY GdaUhd aj Pdc NdGakG ddQCS s
(3Vef eLehY , JQJjHgG (B: (3ef U (B79 - (3U(B149s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B202 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdRGhjI GdMeRGhjI (B(4/127) s
Keywords: (3GdWHs